Implementasi Metode Field Trip Mahasiswa Universitas Sumatera Utara dengan PTPN III Unit Gunung Para dalam Meningkatkan High Order Thinking Skills - Charloq; Yazid, Abu; Alda Vionika Pakpahan, Anisa (Universitas Mataram, 2023)
Field trip as a form of implementation of lectures and practicum methods of Outcome Education-based semester learning plan held at PTPN III Gunung Para Unit, Dolok Merawan District, Serdang Bedagai Regency (Sergai), North Sumatra on Saturday, September 16 2023. The field trip program is a form of implementation of lectures and practicums for semester learning planning methods based on Outcome Education which is carried out at PTPN III Gunung Para Unit, Dolok Merawan District, Serdang Bedagai (Sergai) Regency, North Sumatra as a form of application and at the same time practicing the knowledge obtained in lectures or Link and Match between theory and application in the field of students at the University of North Sumatra (USU) Agrotechnology and Agricultural Engineering Study Program. This activity hopes that students will be able to hone high order thinking skills including problem solving abilities, creative thinking, investigative skills and decision making abilities, especially in the fields of agriculture/plantation of oil palm and rubber commodities.